Strategi Peningkatan Kualitas Guru PAI dalam Manajemen Pembelajaran - Humaira Chairunnisa’; Lutfi Hakim; Suahrul Ramadhan; Gusmaneli Gusmaneli (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
The article is entitled "Strategy for Improving the Quality of PAI Teachers in Learning Management." This article was written because of the poor quality of PAI teacher management in implementing the teaching and learning process. This article focuses on how to improve the quality of PAI teachers in managing learning. The learning process requires learning activities based on concepts and principles to achieve learning goals effectively, efficiently and productively, starting with determining and planning strategies. Teachers play an important role in determining the quantity and quality of learning that takes place. Teachers need to think carefully and make learning plans to improve students’ ability to listen to lessons and master learning objectives to improve the quality of teaching. The pattern above shows that being a teacher and simply providing material to students is not an easy thing and requires a mature strategy as well. Therefore, in this article we will explain learning strategies and learning management that teachers must understand in an effort to improve training and the quality of PBM.